THE INTAKE OF ENERGY, PROTEIN, AND ATHLETES’ STAMINA AT THE CENTER OF EDUCATION AND SPORTS TRAINING FOR LEARNERS OF WEST NUSA TENGGARA - Anak Agung Sagung Putri Chandradewi; Irianto Irianto (poltekkes kemenkes mataram, 2017)
Abstract : Athlete’s performance is not only influenced by the intensity of routine exercise, but also the stamina and nutrition intake in accordance with the requirement baded on sport field. This research objective was to know the intake of energy, protein, and athletes’ stamina at The Center of Education and Sports Training for Learners of West Nusa Tenggara. This study utilized an observational with 40 respondents as sample from five different sport fields whose aged 14 -18 years took purposively. The data collected were nutrition intake through Food recall method 24 hours, nutrition status with Body Mass Indeks and athletes’ stamina by running distance for 12 minutes. The research finding was 95% the nutritional status of most of the athletes in the normal category, the average energy intake 97.5%, and the average protein intake 92.5%, and athlete of stamina was in good performance (67.5%). The athletes with excellent stamina tend in good energy and protein intake.